Komponen Epidemi Penyakit Busuk Akar dan Pangkal Batang Tebu di Sumatera Selatan - Tri Maryono; Ani Widiastuti; Rudi Hari Murti; Achmadi Priyatmojo (Jurnal Fitopatologi Indonesia, 2020)
Epidemic Components of Sugarcane Root and Basal Stem Rot In South Sumatra Root and basal stem rot disease is one of new disease that currently was became a emerging problem on sugarcane plantations in Lampung and South Sumatra. The research was aimed to study the model of disease progression, AUDPC, infection rate (r), and the influence of weather and soil condition (physical and chemical properties of soil) on the development of sugarcane root and basal stem rot disease. The research was conducted on sugar cane plantation in South Sumatra. The disease incidence in three varieties was observed weekly in the field which had infected plant in previous year.. The data were analyzed to develop model of the disease progression, AUDPC, and the rate of root and basal stem rot disease. Weekly weather data was acquired from weather station of Sultan Mahmud Badaruddin Airport, Palembang. Soil sample was taken from three disease category i.e moderate (disease incidence 25,1% - 50%), severe (disease incidence 50,1% - 75%), and healthy (no disease). The results showed that the disease develops following monomolecular and logistic models. The AUPDC and infection rate (r) in the monomolecular model were lower than in the logistic model. The direct effect coefficient of rainfall and relative humidity (RH) on the disease were positive (1.27 and 0.46 respectively), contrary the temperature and duration of irradiation which had a negative coefficient (-0.33 and -0.45 respectively). Meanwhile, K availability and permeability give a positive effect on the disease, while the total N and Fe availability give a negative effect on the disease.